PENGARUH EUSTRESS PERAN, KECERDASAN EMOSIONAL DAN DUKUNGAN SOSIAL KELUARGA TERHADAP KESEJAHTERAAN PSIKOLOGIS MOMPRENEUR - Srimulyani, Veronika Agustini (Universitas Nusantara PGRI Kediri, 2020)
The research objectives were to analyze: 1) the influence of role eustress, emotional intelligence, and family social support on the psychological well-being of mompreneur; 2) the moderating effect of emotional intelligence and family social support on the influence of entrepreneurial eustress on the psychological well-being of mompreneur; by taking studies on married women entrepreneurs in the category of Micro and Small Enterprises (UMK) in Taman Kota Madiun Village. The sampling technique was judgment sampling. The data collection procedure was through distributing questionnaires directly to the respondents to 60 mompreneur with 50 questionnaires returned and only 45 completed questionnaires. Data analysis used moderated regression analysis, processed with the IBM SPSS version 22 program. The results of data analysis showed: 1) Eustress has a significant positive effect on the psychological well-being of mompreneur; 2) Emotional intelligence has a significant positive effect on the psychological well-being of mompreneur; 3) Family social support has a significant positive effect on the psychological well-being of mompreneur; 4) There is no moderating effect of emotional intelligence and family social support on the effect of entrepreneurial eustress on the psychological well-being of mompreneur